Поля напружень порід фронтальної частини Поркулецького покриву Українських Карпат у басейні ріки Чорна Тиса - Гайдук, Т.В. (Геодинаміка, 2009)
The article is devoted to the study of cracks, as sensitive indicators of the tense state of rock. On the basis of research of cracks the reconstruction of the fields of tensions is conducted for the rock of Trostyanets volcanic rock strata and adjoining formation in the basin of the river of Chorna Tysa.